Some questions of responsibility of legal entity on the legislation of Republic of Kazakhstan (Journal of actual problems of jurisprudence, 2018)
The author considers in the article some issues of governing the activity of a legal entity. In particular, the author concentrates on features of corporate governance in such organisational-legal forms of legal entities as limited liability partnership and joint stock company. The special attention in the article is spared also to plenary powers and responsibility of organs of legal entity.Key words: legal entity, joint stock company, liability, participant.